2019
DOI: 10.2174/1874944501912010414
|View full text |Cite
|
Sign up to set email alerts
|

Morningness-Eveningness Chronotypes, Sleep Quality, and Sleepiness Among Nurses

Abstract: Background:Poor sleep quality and sleepiness is a common problem in nurses. The morningness-eveningness preference of nurses may affect their sleep quality.Objective:The objectives of this study were (1) to describe the quality of sleep in a group of hospital nurses and (2) to analyze the effect of shift work and morningness-eveningness on the sleep quality of nurses.Methods:In this cross-sectional study, 120 nurses completed the survey in a university hospital in Iran. The study tools were Pittsburgh Sleep Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…In support of our findings Hajaghazadeh et al also report that a significant relation was found only between shift work and quality of sleep. 16 There was strong negative correlation found between the hours of sound sleep (sleep hours) (r=-0.495; df-90; p-0.000) and the total PSQI score in our study.…”
Section: Resultssupporting
confidence: 46%
See 3 more Smart Citations
“…In support of our findings Hajaghazadeh et al also report that a significant relation was found only between shift work and quality of sleep. 16 There was strong negative correlation found between the hours of sound sleep (sleep hours) (r=-0.495; df-90; p-0.000) and the total PSQI score in our study.…”
Section: Resultssupporting
confidence: 46%
“…The statistically significant association of education (p value-0.003), shift nature (p value 0.005) and alcoholism (p value-0.035) with circadian chronotypes in our study is supported by a study finding by Hajaghazadeh et al where they have reported that the sleepiness of nurses had a significant relation with shift works and marital status (p value <0.05). 16 Marital status (p value-0.021), monthly income level (p value-0.039), tea coffee intake habit (p value 0.017), time gap between dinner and bed time (p value 0.000) and the circadian chronotypes (p value-0.006) showed statistically significant association between quality of sleep among the study participants in our study. In support of our findings Hajaghazadeh et al also report that a significant relation was found only between shift work and quality of sleep.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Práce na směny narušuje kvalitu spánku a fyziologický systém cirkadiánních rytmů člověka a člověk mění svůj režim (7). Sestry jsou vystaveny riziku poruch spánku, nedostatku spánku, špatné kvality spánku (9,10). Špatná kvalita spánku a nedostatek spánku může u sester narušit koncentraci, paměť, pozornost, výkonnost, což může ovlivnit bezpečnost pacientů (3,11,12,13).…”
Section: úVodunclassified